2007
DOI: 10.1183/09059180.00010305
|View full text |Cite
|
Sign up to set email alerts
|

Combination versus monotherapy for nosocomial pneumonia

Abstract: Combination antibiotic therapy of nosocomial pneumonia is sometimes appropriate and desirable; however, it should be used judiciously. When pneumonia appears in the first 5 days following hospital admission and in the absence of other risk factors for infection by multidrug-resistant pathogens, the infection is likely to be due to a pathogen acquired in the community and is likely to be sensitive to most antibiotics.These infections should generally be treated with monotherapy. However, pathogens resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Combination therapy of drug is more effective than individual due to their synergistic effect. Various studies have been reported that a combination therapy is most effective in pneumonia infection [23,24]. Ceftriaxone is third generation class of beta lactam antibiotic while CSE 1034 is a combination of third generation β-lactam antibiotic with sulbactam beta lactamase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy of drug is more effective than individual due to their synergistic effect. Various studies have been reported that a combination therapy is most effective in pneumonia infection [23,24]. Ceftriaxone is third generation class of beta lactam antibiotic while CSE 1034 is a combination of third generation β-lactam antibiotic with sulbactam beta lactamase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…We already distinguish patients with a severe infection; there is evidence that the prognosis in these patients is worse than in patients with a relatively non-severe disease. At the same time, the benefits of, for example, combination antibiotic therapy have not been fully identified [47,48,49,50]. Patients in intensive care units are considered separately, and we recognize that this may not be the severe course of the infection itself, but simply patients in a severe condition by their baseline status, and the infection only makes its own special contribution to the severity of the condition and, of course, to the efficacy of treatment and prognosis.…”
Section: Of 12mentioning
confidence: 99%
“…El tratamiento combinado es utilizado especialmente en pacientes de alto riesgo o que están gravemente enfermos (6).…”
Section: Recomendación 3 Si Es Grave Use Combinaciones De Antibióticos En El Caso De Pacientes En Los Que La Infección Amenaza La Vida Utunclassified